Spatial complex correlation characteristics of carbon emissions and carbon transboundary transfer: Assessment of the carbon footprint in four mega-urban agglomerations in China - Chengxue Yu; Haimeng Lei; Hongbo Zheng; Tong Xu; Zhanfeng Dong (Sustainable Futures)
Urban agglomerations, as the main carriers of, serve as critical platforms for emission reduction and carbon absorption playing a pivotal role in achieving the goals of ''carbon peaking'' and ''carbon neutrality'' targets. This study investigates these issues from the dual perspectives of ''carbon sources'' and ''carbon sinks,'' utilizing a modified gravity model to construct a spatial correlation matrix of carbon footprint pressure. Based on this matrix, we build a spatial correlation network to study urban agglomeration carbon emissions and Carbon transboundary transfer. The study systematically analyzes the structural characteristics of the spatial correlation network of carbon footprints in four Mega-urban agglomerations in China from both macro and micro perspectives. The results show that: 1. Between 2006 and 2021, the per capita carbon footprints of the four mega-urban agglomerations in China exhibited an upward trend. Regions characterized by high industrialization levels and dense populations experienced greater carbon footprint pressures. Economic development and policy-driven factors were found to significantly influence the spatial distribution of carbon footprints. 2. The network density of the four Mega-urban agglomerations in China generally shows an upward trend, indicating that the interregional connections in carbon footprint management and environmental cooperation are continuously strengthening. 3. The spatial correlation networks of regional carbon footprints within the four mega-urban agglomerations were categorized into four functional blocks. These blocks underwent varying degrees of reorganization throughout the study period. 4. Most of the motif structures in the four Mega-urban agglomerations in China exhibit characteristics of reciprocity, circularity, and aggregation. This indicates the dominance a ''broker-like'' collaborative mechanism that optimizes the allocation of environmental resources across regions and enhances the overall synergistic effects of regional low-carbon transformation. Based on these findings, the study advocates for differentiated emission reduction and carbon absorption policies tailored to the specific roles and development needs of each urban agglomeration. These policies should be implemented locally and subsequently expanded to the entire urban agglomeration. By overcoming regional limitations and promoting systematic collaboration, such measures aim to foster synergy among regions, ultimately forming a complementary and collaborative green transformation framework across urban agglomerations.